La cultura financiera y niveles de endeudamiento de los miembros de las asociaciones comerciales del Mercado Municipal de Tosagua - Baquerizo Salguero, David Raúl (2025)
The following research determines the financial culture and debt levels of the members of the associations of the Municipal Market in Tosagua canton through the fulfillment of specific objectives with their respective activities. In the first phase, a diagnosis of the current situation of the association members was conducted by applying a survey to the study participants. Then, in the second phase, the financial products accessible to them were characterized, along with an analysis of the applied instrument. Additionally, an interview was conducted with the association leaders to analyze financial culture behavior. Finally, in the third phase, an action plan was developed using the 5W+2H matrix, outlining strategies recommended for strengthening financial culture to enhance financial education within the Municipal Market associations. Through the completion of all planned activities, the expected results were successfully achieved.